Are Predicted Lifetime Consumption Profiles Robust with respect to Model Specifications? - Tom Kornstad (Statistics Norway, Research Department, 2001)
Structural models of lifetime labour supply and consumption require functional specifications of preferences as well as other assumptions that can be difficult to assess a priori. Misspecifications of the model might lead to biases in the estimates of preferences, that may influence the simulation results obtained from the model. In this paper we study to what extent predicted distributions of lifetime consumption are robust with respect to the specification of preferences. The simulation results show that simulated distributions of lifetime consumption strongly depend on the estimate of the intertemporal substitution rate as well as on the estimate of the time preference rate relative to the marginal interest rate net of taxes.
Keywords: D91; C52; D12; 330; Lifetime preferences; life cycle consumption; testing modelspesifications; empirical models.